Development and deployment of transgenic plants: biosafety considerations - Sharma, K.K.; Sharma, H.C.; Seetharama, N.; Ortíz, R. (Springer, 2002)
Recombinant DNA technology has great potential to enhance and extend the advantages of conventional plant breeding, and increase the production and productivity of crops to meet the increasing demand for food and food products in the future. Judicious application of this technology provides opportunities for alleviating some of the major constraints to crop productivity under subsistence farming conditions in the developing countries. Considerable progress has been made in developing strategies for the production and deployment of transgenic crops. However, biosafety concerns have been raised regarding the deployment and release of genetically engineered plants. This debate has divided the farming and consumer communities over acceptability of genetically modified foods. There is a need for a thorough investigation regarding the fate of transgenic plants in the environment, and their interaction with wild relatives and non-target organisms. The production and release of transgenic plants should be based on experience and sound scientific reasoning. The regulatory requirements for deployment of transgenic crops should be streamlined and harmonized, in order to achieve sustainable food production, poverty reduction, and environmental protection in resource-poor countries in the semi-arid tropics.